MPI vs OpenMP: A case study on parallel generation of Mandelbrot set - Soto Gómez, Ernesto (2020)
Nowadays, some of the most popular tools for parallel programming are Message Passing Interface and Open Multi-Processing. It is of interest to compare these tools in solving the same kind of problems, because of the use of different approaches to inter-task communication. This work attempts to contribute to this goal by running trials in a centralized shared memory architecture in the case of problems with an entirely parallel solution. The selected case study was the parallel computation of Mandelbrot set. Trials were conducted for different iteration limits, processors amount, and C++ implementation variants. The results show better performance in the case of Open Multi-Processing.